Increased rainfall remarkably freshens estuarine and coastal waters on the Paciﬁc coast of Panama: Magnitude and likely effects on upwelling and nutrient supply. - Valiela, Ivan (2012)
Increased intensity of rainfall events during late 2010 led to a remarkable freshening of estuarine, near- and off-shore waters in coastal Pacific Panama. The increased rain intensity during the wet season of 2010 lowered salinity of estuarine and coastal waters to levels unprecedented in previous years. Fresher conditions were most marked within estuaries, but even at 6 km from shore, salinities were 8–13‰ lower during the 2010 wet season, compared to a lowering of up to 2‰ during previous wet seasons. Freshwater added to surface waters by rain had major biological, hydrodynamic, and biogeochemical consequences, increasing stream erosion, uprooting stream-edge terrestrial and mangrove trees, increasing mortality of benthic fauna, damping upwelling of denser, nutrient-rich water that was expected given the contemporaneous most intense La Niña in decades, as well as by enriching surface seawater by direct deposition and by horizontal advection of nutrients from land. It appears that wet season rainfall is slowly increasing in the region, and if the level of rainfall reported here is a harbinger of future climate change effects on land-sea couplings in tropical coastal ecosystems, the resulting freshening could significantly shift biogeochemistry and coastal food webs in the region and elsewhere.